2013
DOI: 10.1530/eje-12-1057
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous hydrocortisone administration for emergency use in adrenal insufficiency

Abstract: Objective: Evaluation of the pharmacokinetics and safety of s.c. hydrocortisone injection for use in adrenal emergency. Design: Single-center, open-label, sequence-randomized, crossover study in a tertiary care center. Patients and methods: Twelve patients with chronic Addison's disease. Comparison of hydrocortisone pharmacokinetics after s.c. and i.m. injection (100 mg) and after s.c. administration of sodium chloride (0.9%) respectively at three different visits. Main outcome measure: maximum serum cortisol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 16 publications
0
43
0
3
Order By: Relevance
“…Reducing barriers to self-injection are most important in my view and the ease of s.c. injection far outweighs the short delay (11 min) in reaching concentrations above 1000 nmol/l (22 min compared with 11 min after i.m. injection) (76). This small time difference compares very favourably with current time lines from contacting health professionals until their eventual hydrocortisone injection in impending crisis (43).…”
Section: Patient Educationmentioning
confidence: 68%
See 1 more Smart Citation
“…Reducing barriers to self-injection are most important in my view and the ease of s.c. injection far outweighs the short delay (11 min) in reaching concentrations above 1000 nmol/l (22 min compared with 11 min after i.m. injection) (76). This small time difference compares very favourably with current time lines from contacting health professionals until their eventual hydrocortisone injection in impending crisis (43).…”
Section: Patient Educationmentioning
confidence: 68%
“…Importantly, we have recently demonstrated that s.c. hydrocortisone is rapidly absorbed with only a short delay compared with i.m. injection (76). Patients clearly prefer s.c. over i.m.…”
Section: Patient Educationmentioning
confidence: 99%
“…The high number of cases without parenteral application of a glucocorticoid in spite of repeated vomiting might be reduced if -instead of i.m. injection -s.c. glucocorticoid injection or a 'hydrocortisone pen' could be established for emergency use in the future (8,32,33). As problems related to a lack of experience among health professionals are characteristic of rare diseases and not unique to CAH, they might be overcome by a generally raised awareness about these so-called 'orphan diseases' in the healthcare system (31).…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous hydrocortisone administration has been recently shown to achieve adequately high serum cortisol levels in only 11 minutes longer than intramuscular administration. 42 While absorption may be reduced in a patient with shock, if more patients are able to administer hydrocortisone at an earlier time, then this may prove to be beneficial. 43 …”
Section: Self-administration Of Intramuscular Hydrocortisonementioning
confidence: 99%